Depression and physical disability in chronic pain: The mediation role of emotional intelligence and acceptance - Joana Costa; João Marôco; José Pinto‐gouveia; Nuno Ferreira (Australian Journal of Psychology, 2017)
Objective Emotional intelligence (EI) and acceptance have previously been identified as potential factors in the adjustment to chronic pain (CP). This study examined the associations between CP experiences, depression, and physical disability. It further investigated the mediating effect of EI and acceptance in the relationship between CP experiences, depression, and physical disability and how this changes with the duration of the CP. Method A cross‐sectional design, employing validated questionnaires, was used to measure pain experience, physical disability, depression, EI, and acceptance in 133 CP patients. Results All variables were found to be significantly associated in theoretically predicted ways. The relationship between CP experiences and depression was mediated by both factors, as high EI and acceptance promoted a decreased influence of pain on depression. By contrast, the relationship between CP experiences and physical disability was mediated by acceptance, but not by EI. Further, the temporal stability analysis of this mediation model showed that long‐term CP patients are better able to make use of these factors. Conclusions The relationship between the experience of pain and depression or physical disability seems to be significantly mediated by factors such as EI and acceptance. This study lends further support to the development of more encompassing models that take both control and non‐control variables into account when conceptualising the adjustment to CP. Theoretical and clinical implications are discussed.